Genome-wide scanning for candidate lethal genes associated with early embryonic mortality in Holstein dairy cattle - Rezaei, Somaye; Shadparvar, Abdol Ahad; Baneh, Hasan; Ghovvati, Shahrokh (Frontiers in Animal Science, 2025)
ObjectiveEmbryo death in the early stages, primarily caused by lethal alleles in the homozygous state, is one of the important challenges in dairy cattle breeding. The availability of large-scale genomic SNP data has proven to be a promising tool for identifying recessive genetic defects. This study was conducted to identify lethal alleles and genes causing embryo death in Holstein dairy cattle using omics data in genomic and transcriptomic level.MethodsHigh-density Bovine770K SNP array genotypes of 3117 samples and whole-genome sequences (WGS) of 743 cows were utilized to identify lethal SNPs, defined as those markers significantly departing from Hardy–Weinberg equilibrium and lacking one of the homozygous genotypes.ResultsThe potential candidate lethal SNPs are harbored by PARD3, BAHD1, FZD3, ERGIC2, IQCN, PROK1, PCTP, SH3GLB1, and RASSF5 genes, according to the ARS-UCD1.2 Bos taurus genome assembly. Transcriptome analysis showed that these genes are steadily expressed in the various embryonic tissues during different stages of embryo development, and therefore were considered as the potential candidate lethal genes. These genes play important roles in various biological processes of embryo development and prenatal survival ability in dairy cattle embryos. These genes contribute to the important embryo lethality-related mechanisms, including the regulation of cell polarity, placental development, phospholipid transport, and apoptosis.ConclusionThe findings of this study provide insight into the complex molecular mechanisms of embryo mortality at the early stage of pregnancy caused by genes following the recessive inheritance model.